Medical Rehabilitation And Geriatric Depression Scale (GDS) Score In The Post Stroke Geriatric Patientsk E - Gunawan, Karina N; Daeng, Bonaventura Handoko; Cecilia, Cissy (JOURNAL OF WIDYA MEDIKA JUNIOR, 2020)
Introduction: Post-stroke depression ranged between 11-68% depends on patient's diversity, diagnostic criteria, and duration between follow-ups after a stroke attack. Prevalence may increase due to the patient's age. Medical rehabilitation and psychotherapy are a necessary effort to help patients overcome their disability. Medical rehabilitation for post-stroke patients includes restoring body functions, handling comorbid dysfunction, exercising individual independence, increasing quality of life, and preventing stroke recurrence. Aim: The objective of this research is to look for the correlation between medical rehabilitation and GDS Score in post-stroke geriatric patients. Methods: This research is an analytical observational with 1 group cohort time approach. The population is post-stroke geriatric patients who go through medical rehabilitation in Primasatya Husada Citra Hospital Surabaya. Result: Using the Chi-Square Test, the value of p is 1. After two weeks of medical rehabilitation, this shows that there is no significant correlation between medical rehabilitation and changes in the GDS score in post-stroke geriatric patients. The value of the odds ratio is 2,333. Conclusion: there was no significant effect of medical rehabilitation on GDS scores in elderly patients after stroke.